The self–directed learning readiness and self–efficacy of nursing students in synchronous learning: A cross–sectional study - Harjanto, Totok; Gautama, Made Satya Nugraha; Sumunar, Dimas Septian Eko Wahyu (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Beyond the pandemic, synchronous online learning was found to be a reliable approach in undergraduate nursing education. The students' self-directed learning readiness and online self-efficacy are key to the successful implementation of this approach. Readiness determines the learner’s needs based on contextual education, while efficacy refers to the students' confidence when completing online learning tasks. Purpose: The current study aims to investigate the relationship between self-directed learning readiness and self-efficacy among undergraduate nursing students. Methods: A descriptive correlational study was carried out to measure the undergraduate nursing students’ readiness and efficacy using the Self-Directed Learning Readiness (SDLR) Scale and the Online Learning Self-Efficacy Scale. Upon completing data collection using a web-based survey, univariate descriptive and bivariate analysis with Pearson correlation were conducted. Results: A total of 188 undergraduate nursing students participated in this study with an average age of 20.12 years old. The majority of nursing students (72.9%) within the program had a moderate SDLR level, while the mean (SD) SDLR was 149.95 (±12.24). Similarly, moderate self-efficacy was reported by the present study participants. The self-efficacy subscale of strength was categorized as high, while moderate levels of generality and magnitude were interpreted from the findings. The bivariate statistical analysis indicated a significant correlation between SDLRS and online self-efficacy (r=0.298, p<0.001). SDLR had significant correlations with each online self-efficacy subscale, including strength (r=0.259, p<0.001), generality (r=0.259, p<0.001), and magnitude (r=0.259, p<0.001). Conclusions: In synchronous learning, the undergraduate nursing student’s SDLR was found to have a positive relationship with self-efficacy. Provisioning the students’ individual learning skills is necessary to enhance their readiness and consequently improve their acquisition of the educational outcomes.